2005
DOI: 10.1113/jphysiol.2005.087734
|View full text |Cite
|
Sign up to set email alerts
|

Proton sensitivity of ASIC1 appeared with the rise of fishes by changes of residues in the region that follows TM1 in the ectodomain of the channel

Abstract: The acid-sensitive ion channel 1 (ASIC1) is a neuronal Na + channel insensitive to changes in membrane potential but is gated by external protons. Proton sensitivity is believed to be essential for the role of ASIC1 in modulating synaptic transmission and nociception in the mammalian nervous system. To examine the structural determinants that confer proton sensitivity, we cloned and functionally characterized ASIC1 from different species of the chordate lineage: lamprey, shark, toadfish and chicken. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…23,25,42), consistent with the hypothesis of the paper of the first ASIC structure (25) that the interaction between the thumb and the ␤-ball is critically involved in the activation process. Further confirming the importance of the thumb, residues at the lower end of the thumb helix ␣5 (Asp-357, Gln-358, and Glu-359) also affect ASIC activation when mutated (22,41). We show here that Glu-315 and Glu-355 in the thumb and Glu-235 and Glu-254 on different loops originating in the ␤-ball are involved in SSIN.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…23,25,42), consistent with the hypothesis of the paper of the first ASIC structure (25) that the interaction between the thumb and the ␤-ball is critically involved in the activation process. Further confirming the importance of the thumb, residues at the lower end of the thumb helix ␣5 (Asp-357, Gln-358, and Glu-359) also affect ASIC activation when mutated (22,41). We show here that Glu-315 and Glu-355 in the thumb and Glu-235 and Glu-254 on different loops originating in the ␤-ball are involved in SSIN.…”
Section: Discussionsupporting
confidence: 54%
“…Different strategies have been employed to identify residues involved in ASIC pH dependence. Coric et al (22) identified regions that are different between pH-gated and nonpH-gated ASICs. Paukert et al (23) mutated conserved acidic and basic side chains in rat ASIC1a, and Smith et al (24) explored differences in the sequence of the H ϩ -activated ASIC2a and the non-gated ASIC2b, mutating acidic residues of ASIC2a that were not conserved in ASIC2b.…”
mentioning
confidence: 99%
“…Interestingly, these residues make contact around Glu 178 and Arg 176 of the adjacent subunit, residues that fall within the second region (residues 87-197) that we find necessary and sufficient for high affinity proton sensing. Further support for the importance of these regions comes from previous data indicating that Asp 351 , Gln 358 , and Asn 359 are required in Lamprey ASIC1a to form active ASIC1a channels, suggesting that these residues are critical for proton-dependent gating (37). We find that mutations Q358E and E355K increase the apparent proton sensitivity of ASIC1a.…”
Section: Discussionsupporting
confidence: 49%
“…Experiments using chimeras composed of proton-insensitive and proton-sensitive ASICs suggest that specific residues within the wrist domain of ASICs are required for proton-dependent activation (35)(36)(37). Channels that are unresponsive to protons are produced when these residues are mutated, and because some of these residues can be titrated by protons, it has been suggested that they represent the proton-binding site(s).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results provide only circumstantial evidence that the post-TM1 domain has a general role in H ϩ gating of ASICs. However, a different study also found that the post-TM1 domain is crucial to distinguish H ϩ -sensitive from H ϩ -insensitive ASICs (32). Moreover, there is much more circumstantial evidence from other studies that reinforce the idea that the post-TM1 domain plays an important role in the gating of ion channels from the degenerin/epithelial sodium channel gene family.…”
Section: Discussionmentioning
confidence: 48%